(untitled) (The Review of Diabetic Studies, 2025)
Infection prevention and control (IPC) remains a cornerstone of modern healthcare, particularly in light of emerging infectious diseases and the persistent threat of healthcare-associated infections (HAIs). This academic research explores the multifaceted role of health practitioners in mitigating the transmission of infections within healthcare settings. Health practitioners, including nurses, physicians, infection preventionists, and support staff, are pivotal in implementing standard precautions, transmission-based measures, and antimicrobial stewardship programs to safeguard patients, colleagues, and the community. Drawing from systematic reviews, guidelines from organizations such as the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC), and empirical studies, this paper examines key principles of IPC, specific responsibilities of practitioners, effective strategies, barriers to compliance, and future directions. Findings underscore that while knowledge of IPC is generally adequate among practitioners, compliance is influenced by factors like training, resource availability, and workload. Enhancing education, leadership support, and technological integration can significantly reduce HAIs, which affect millions annually and contribute to antimicrobial resistance. This comprehensive analysis, spanning approximately 30 pages in standard academic formatting (double-spaced, 12-point font), advocates for a multidisciplinary approach to empower health practitioners as frontline defenders against infection transmission. Recommendations include mandatory ongoing training, policy enforcement, and research into behavioral interventions to bridge the knowledge-practice gap.